FAKTOR HEREDITAS DALAM MEMBENTUK KARAKTER ANAK SEKOLAH DASAR - Irka Saliha; Siti Rokmanah; Nana Hendracipta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
behavior that arises from students. The research in this article is in the form of books and various sites on the internet related to heredity factors. Data collection in this research article is document study. Based on the results of the study, heredity factors in individuals are seen to be very influential in physical development (the human body), such as the color of the eyes, skin, hair type, and others. The heredity factor is one of the factors in the process of forming the characteristics of each individual. This factor is an innate or hereditary factor from parents to a child, both physically and psychologically from the time of conception. This research aims to examine more deeply the heredity factor in forming character, especially in students or students as objects in learning. But for children who experience unfavorable heredity factors, teachers can provide strategies for these children to improve. Therefore, in elementary school (SD) it is very possible for various kinds of child development like this.